The effect of the monthly thermal anomaly of the surface waters of the Mediterranean Sea and its relationship to the recurrence of the Mediterranean depression over Iraq - Mohammed Wheed Hassan Hussein Al-Saadi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The oceans play a major role in energy storage in the global system of land, oceans and atmosphere. In this context, knowledge of the past evolution and future trends of sea surface temperature is critical for future climate scenarios. Previous studies have highlighted the role of sea surface temperature as an important component in the development/or intensification of heavy precipitation events in the western Mediterranean basin but also highlighted its role in heat waves in Europe. In the Mediterranean thermal anomaly, as the autumn season and during November for the years (2013, 2015, 2016, 2019) recorded about (7, 6, 7, 7) repetitions / respectively, which was associated with an increase in the values of the Mediterranean thermal anomaly, while the winter season and January The highest frequency was recorded for the years (2012, 2013, 2014, 2019) about (8, 7, 6, 6) iterations, and this increase was associated with the relative decrease in the Mediterranean thermal anomaly.